Factors Influencing Diversion from State Mental Health Hospitals - Marty, Douglas A (International Journal of Psychosocial Rehabilitation, 2014)
Objective: While there has been much research on predictors of psychiatric hospitalizations there has been little research on the community resources, supports and processes used to divert a hospital episode. The pur - pose of this study is to address this gap by studying (1) the community resources available as an alternative to state psychiatric hospitalization; and (2) the practices exhibited when determining whether state hospitalization is necessary. Methods: A mixed methods design was developed. The purpose of the first arm was to assess what non-hos- pital resources were available to mental health centers. The second arm looked at the processes center staff goes through in determining hospitalization or community diversion. Results: Differences were noted between centers with high and those with low diversion rates. Centers that tended to use the state hospital less had more community diversion resources available, had an agency philo - sophy aimed at diversion, and used processes which included shared decision-making. Further, staff had more experience and established protocols to ensure follow-up services were in place. Conclusions: Agencies that fostered a philosophy and protocol focusing on community diversion, provided Objective: While there has been much research on predictors of psychiatric hospitalizations there has been little research on the community resources, supports and processes used to divert a hospital episode. The pur - pose of this study is to address this gap by studying (1) the community resources available as an alternative to state psychiatric hospitalization; and (2) the practices exhibited when determining whether state hospitalization is necessary. Methods: A mixed methods design was developed. The purpose of the first arm was to assess what non-hos- pital resources were available to mental health centers. The second arm looked at the processes center staff goes through in determining hospitalization or community diversion. Results: Differences were noted between centers with high and those with low diversion rates. Centers that tended to use the state hospital less had more community diversion resources available, had an agency philo - sophy aimed at diversion, and used processes which included shared decision-making. Further, staff had more experience and established protocols to ensure follow-up services were in place. Conclusions: Agencies that fostered a philosophy and protocol focusing on community diversion, provided Objective: While there has been much research on predictors of psychiatric hospitalizations there has been little research on the community resources, supports and processes used to divert a hospital episode. The pur - pose of this study is to address this gap by studying (1) the community resources available as an alternative to state psychiatric hospitalization; and (2) the practices exhibited when determining whether state hospitalization is necessary. Methods: A mixed methods design was developed. The purpose of the first arm was to assess what non-hos- pital resources were available to mental health centers. The second arm looked at the processes center staff goes through in determining hospitalization or community diversion. Results: Differences were noted between centers with high and those with low diversion rates. Centers that tended to use the state hospital less had more community diversion resources available, had an agency philo - sophy aimed at diversion, and used processes which included shared decision-making. Further, staff had more experience and established protocols to ensure follow-up services were in place. Conclusions: Agencies that fostered a philosophy and protocol focusing on community diversion, provided alternative resources for consumers in crisis, and had adequate monitoring and training increased diversion rates and avoided unnecessary hospitalizations